Seven men : and the secret of their greatness - Metaxas, Eric. (Nashville : Thomas Nelson, 2013)
"What makes a great man great? 'Seven Men' offers answers in the captivating stories of some of the greatest men who have ever lived. In this gallery of greatness, seven historical figures come to life as real people who experienced struggles and challenges that probably would have destroyed the resolve of most other men. What was their secret?..."--Dust jacket flap.
George Washington -- William Wilberforce -- Eric Liddell -- Dietrich Bonhoeffer -- Jackie Robinson -- Pope John Paul II -- Charles W. Colson.
Includes bibliographical references and index.
Keywords: Washington, George, -- 1732-1799.; Wilberforce, William, -- 1759-1833.; Liddell, Eric, -- 1902-1945.; Bonhoeffer, Dietrich, -- 1906-1945.; Robinson, Jackie, -- 1919-1972.; John Paul -- II, -- Pope, -- 1920-2005.; Colson, Charles W; Success; Leadership